A Comparison of preprandial mixed insulin given three times daily and basal-bolus insulin therapy started postoperatively on patients having coronary artery bypass graft surgery [Koroner arter bypass cerrahisi geçiren hastalarda 3'lü karışım ve 4'lü yoǧun i̇nsülin tedavilerinin karşılaştırılması] - (:unkn) unknown (Marmara University, 2012)
Objective: Insulin therapy initiated after coronary artery bypass graft (CABG) surgery has decreased long-term mortality. The aim was to compare the effectiveness of prandial premixed therapy (PPT) using insulin thrice daily and basal-bolus therapy (BBT) on patients having CABG surgery. Patients and Methods: Thirty-four patients having CABG surgery were included. Fasting blood glucose (FBG), postprandial blood glucose (PPBG), hemoglobin A1c (HbA1c) and hemoglobin levels were determined preoperatively and at the first week postoperatively when the patients were randomized to either PPT or BBT. Initial measurements were repeated at the end of three months. Results: Seventeen patients (F/M:9/8; 61.5±8.5 years) were assigned on a random basis to the mixed insulin arm and 17 patients (F/M:10/7; 57.4±9.2 years) to the basal-bolus arm. FBG, PPBG and HbA1c levels of both groups (7.6±0.8 % vs 6.7±0.5 % in the BBT and 7.3±0.7 % vs 7.3±1.0 % in the PPT group) at the end of the 3 months were not different than at the time of randomization. The percentage of patients reaching HbA1c levels below 6.0%, 6.5% and 7.0% were higher in the BBT group compared to the PPT group. Conclusion: For patients who had undergone CABG surgery, BBT provided more patients with HbA1c levels below the target than did PPT. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Basal-bolus insulin therapy; Coronary artery bypass graft surgery; Premeal mixed insulin therapy